Factors related to delay in cervical cancer diagnosis and treatment among women in Bangladesh: A cross-sectional study - Hoque, Md Moinul; Nahar, Nasreen; Mahbub, Md Shahriar; Akter, Jesmin; Ara, Begum Rowshan (Journal of Biomedical Sciences, 2023)
Background: Bangladesh has a large proportion of women at risk of developing cervical cancer. Though it is considered preventable, it is the second commonest cancer of women in Bangladesh. This study explored the factors influencing the delays in seeking cervical cancer care.Material and methods: Three hundred and ninety nine (399) randomly selected women with cervical cancer attending clinical care in a tertiary hospital were enrolled. Both quantitative and qualitative methods were followed. Face-to-face interviews using a semi-structured and in-depth questionnaire were carried out. The univariate analysis measured the association with statistical significance set at p